2022
DOI: 10.1108/ilt-08-2021-0326
|View full text |Cite
|
Sign up to set email alerts
|

Friction condition of aluminum alloy AA6061 lubricated with bio-lubricant in cold forging test

Abstract: Purpose Cold forging operation is one of the widely used techniques in industry production. This paper aims to present a case study in highlighting and modelling the use of different type of palm oil-based [palm stearin (PS), palm kernel oil (PKO) and palm mid olein (PMO)] as a bio-lubricant in cold forging process using experimental and finite element method. Design/methodology/approach Ring compression test plays a fundamental role in the understanding of materials science and engineering because of the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…As stated by Yahaya and Samion, 2 CMFO is fully formulated lubricant, and may demonstrate sluggish movement during forging processes. As a consequence, friction and compression force seem to be reduced during the transition period and metal-to-metal contact between the die and the work material was minimal.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…As stated by Yahaya and Samion, 2 CMFO is fully formulated lubricant, and may demonstrate sluggish movement during forging processes. As a consequence, friction and compression force seem to be reduced during the transition period and metal-to-metal contact between the die and the work material was minimal.…”
Section: Resultsmentioning
confidence: 93%
“…Friction is one of the key factors for evaluating the tribological performance of palm oil in metal forming process. Zhang et al, 16 has proposed the used of two friction model that is Coulomb friction factor (CFC) as presented in equation ( 1) and Tressa shear factor (TSF) represented equation (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, owing to poor formability of aluminium and aluminium alloys at room temperature, friction tests of alloys focus on plastic working in warm and cold forming conditions. Yahaya and Samion [ 31 ] analysed the friction condition of AW-6061 aluminium alloy lubricated with bio-lubricant in a cold forging test. It was found that the palm oil-based lubricant has good performance compared to a mineral-based oil in terms of surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…It also goes by the name of palm olein and is most frequently used as cooking oil. Palm oil can be used as an industrial lubricant due to its longer hydrocarbon chain and low unsaturation (Yahaya and Samion, 2022). The number of unsaturated fatty acids and the length of the fatty acid chain both have an effect on the viscosity of palm oil.…”
Section: Introductionmentioning
confidence: 99%